Gender Influence of PhET Simulation on Students’ Score Level - Alabi, Abdul-Hafiz Abolade; Mohammed, Ridwan Enuwa; Yusuf, Aishat A (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
Students' performances are often compared and evaluated based on their score levels. Poor performance across each score level can be linked to the general perception of physics as a complex subject due to its abstract and calculative nature. Hence, to help improve students’ performance across each score level, this study investigated the influence of innovative simulations on students’ performance and retention based on their score levels and gender. This study adopted a quasi-experimental non-randomized 2×2×3×2 factorial design. A purposive sampling technique was used to choose two schools with 55 students in Ilorin, Kwara state. The research instruments include a Physics Education Technology (PhET) simulation developed by the University of Colorado Boulder, a Physics Performance Test (PPT), and a Physics Retention Test (PRT). The reliability of the performance and retention test was determined using KR-21 with indices values of 0.855 and 0.769 correspondingly. The findings revealed that the use of computer simulation had a positive effect on the performance and retention in terms of the score levels and had a significant impact on the student's performance and retention with a t-value (-3.13);p<0.005 and t-value (-3.69); p-value< 0.005 respectively. Also, it established that the female students performed better than the male students across different score levels. It was concluded that computer simulation affected the students' performance and retention based on score levels and gender. Therefore, it is recommended that computer simulation be used in the teaching and learning process for better conceptual understanding of the students at different score levels.